2012
DOI: 10.3109/00016489.2012.681798
|View full text |Cite
|
Sign up to set email alerts
|

Nasal obstruction and rhinorrhea reflect nonspecific nasal hyper-reactivity as evaluated by cold dry air provocation

Abstract: VAS scores for nasal obstruction, rhinorrhea, and sneezing were significantly higher in groups A and B than in group C before and after CDA provocation. Change of nasal obstruction and rhinorrhea was significantly larger in group A compared with group B or C. There were also significant differences in the amount of rhinorrhea between groups. All these parameters significantly correlated with the change of MCA values after CDA provocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Nasal congestion might be associated with the turbinate swelling, and rhinorrhea with increased nasal secretion. The result was partly consistent with previous studies (16,21,22,24) . Sneezing is considered to be an irrelevant nasal symptom in most studies, which was in accordance with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Nasal congestion might be associated with the turbinate swelling, and rhinorrhea with increased nasal secretion. The result was partly consistent with previous studies (16,21,22,24) . Sneezing is considered to be an irrelevant nasal symptom in most studies, which was in accordance with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…11 In our previous study, we indicated that changes in nasal obstruction and rhinorrhea were more important in evaluation of NHR using CDA provocation machinery. 12…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier researchers studying CDA had adopted ~10°C, as a result of our several studies, we have shown that 0°C air was equally efficient for evaluation of NHR with less discomfort for patients. 79,12…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations